A 10-year retrospective evaluation of UVA-1 phototherapy in a Latin American tertiary center : clinical profile and therapeutic outcomes (2025)
Background: Ultraviolet A1 phototherapy is a well-established treatment for various dermatological conditions, including sclerodermiform diseases, inflammatory dermatoses, and cutaneous lymphomas. Despite its widespread use, there is limited data on its efficacy and safety in Latin American populations. This study aimed to characterize the clinical profile and therapeutic outcomes of patients treated with UVA1 phototherapy at a tertiary center in Colombia over a 10-year period. Methods: A retrospective, cross-sectional study was conducted using the medical records of 281 patients who received ultraviolet A1 phototherapy between 2014 and 2024. Sociodemographic, clinical, and treatment-related variables were analyzed. Treatment response was evaluated based on changes in body surface area involvement and classified as either worsening or improvement, with the latter further categorized into three groups: 0–25%, 26–75%, and 76–100%. Results: The cohort comprised 71.1% females, with a median age of 48 years. The most common conditions were sclerodermiform diseases (58%, predominantly morphea), inflammatory dermatoses (22.4%, including atopic dermatitis and prurigo), and cutaneous lymphomas (14.6%, mainly mycosis fungoides). A positive effect was observed in 88.7% of cases, with 16% achieving >76% in body surface area involvement reduction. Sclerodermiform diseases showed the highest stability (56.4% with 0% of change in BSA), while inflammatory conditions and lymphomas exhibited higher rates of significant improvement (27% and 39%, respectively). High cumulative doses (>975 J/cm²) were associated with better outcomes, particularly in lymphomas and sclerotic disorders. Overall, 75.1% of patients experienced no adverse events, with tanning (8.9%) and pruritus/pain (5%) being the most frequent.